2018
DOI: 10.1111/1759-7714.12952
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of blood neutrophil‐related indices during nivolumab treatment may be associated with response to salvage chemotherapy for non‐small cell lung cancer: A hypothesis‐generating study

Abstract: Several recent studies have shown that salvage chemotherapy following PD‐1 blockade produces high antitumor activity in some patients with non‐small lung cancer (NSCLC). However, the underlying synergistic mechanisms remain uncertain. The blood neutrophil‐to‐lymphocyte ratio (NLR) and absolute neutrophil count (ANC) can reflect the number of circulating myeloid‐derived suppressor cells and tumor‐associated neutrophils. The immunosuppressive status of the tumor microenvironment could be monitored by the time‐se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…In addition to the observed effect on lymphocyte immuno-phenotype, the active components of ganoderma spore powder inhibited the expression of iNOS and COX-2, as well as TNF-α and IL-6, through the suppression of LPS-based activation of NF-κB in RAW264.7 cells [32][33]. Similarly, we presented very interesting data on Th1/Th2 cell drift.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In addition to the observed effect on lymphocyte immuno-phenotype, the active components of ganoderma spore powder inhibited the expression of iNOS and COX-2, as well as TNF-α and IL-6, through the suppression of LPS-based activation of NF-κB in RAW264.7 cells [32][33]. Similarly, we presented very interesting data on Th1/Th2 cell drift.…”
Section: Discussionsupporting
confidence: 64%
“…Lymphocyte counts indicate anti-tumor immunity [13]. A previous study con rmed that ganoderma spore powder inhibits the production of TNF-α and IL-6 preventing sustained immune response [32]. Against these data, surprisingly, we showed by multivariate analysis that low AGR was an independent poor prognostic factor related to PFS in the e cacy of ganoderma spore powder (HR = 1.572, p = 0.038).…”
Section: Discussionmentioning
confidence: 66%
“…On the other hand, lymphocytes have been shown to be effective suppressors of cancer progression and to reflect host immunity [ 18 ]. And the NLR may be a more useful prognostic factor than the isolated leukocyte fraction as a marker reflecting both inflammation and the immune system function [ 4 , 17 , 18 , 19 , 20 , 21 ]. CRP and NLR have been studied as a prognostic biomarker of nivolumab in several cancers including NSCLC, metastatic renal cell carcinoma, metastatic melanoma, and R/M HNSCC [ 13 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with progressive disease status after ICI treatment, another therapy sometimes could be administered to extend their life. Several studies have reported that salvage chemotherapy (SCT) administered after immunotherapy would be effective for patients with metastatic non-small-cell lung cancer (NSCLC), metastatic melanoma, B cell lymphoma, advanced gastric cancer, and metastatic urothelial carcinoma [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Furthermore, SCT has been reported to be an effective treatment for HNSCC in R/M as well as other carcinomas and is attracting attention as a sequential treatment [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional proposed markers of response include neutrophil‐to‐lymphocyte ratio (NLR), which has been reported to increase over time in non‐responders and decrease in responders, and inflammatory cytokines, which have also been correlated with response rates and toxicity 72–78 (Figure 3). Myeloid‐derived suppressor cell (MDSC) levels have been used to predict therapy response or resistance to ipilimumab treatment in metastatic melanoma patients, where increased frequency was associated with decreased efficacy, and vice versa 79,80 .…”
Section: Novel Ici Approaches To Precision Oncologymentioning
confidence: 99%